Frequency and intensity of menopausal symptoms in relation to temperament, personality and coping style - Bielawska-Batorowicz, Eleonora (Menopause Review/Przegląd Menopauzalny, 2007)
Objectives: Psychological theories explain the mechanisms which link personality and health. These theories point to neuroticism and some temperamental traits as risk factors for diseases and low subjective evaluation of health. The aim of the studies was to examine the role of personality, temperament and coping style as moderators of menopausal symptoms. Design: The studies were designed as cross-sectional. All measures were taken at the same time. Material and methods: Three hundred and six women aged 45-55 yrs participated in two research projects. Subjects had at least 12 years of education, were married with children, and were not affected by artificial menopause. The questionnaires administered included a scale to measure frequency and intensity of menopausal symptoms (Moje samopoczucie), NEO-FFI Inventory, a temperament questionnaire (FCZ-KT) and a scale to measure women’s opinions on menopause. Results: The evaluation of frequency and intensity of menopausal symptoms was linked to hormonal replacement therapy – those on HRT scored lower indicating less intense and less frequent symptoms. The correlation and regression analyses indicated the significant relations of symptoms” frequency and intensity with high neuroticism, reactivity, emotion-oriented and avoidance-oriented coping. These findings were irrespective of HRT. Conclusions: Psychological factors may modify the presentation of menopausal symptoms and influence patients’ decisions regarding hormonal treatment.